Eating Behavior: How Food Safety Knowledge and Attitude Influence Individual’s Food Choices - Kusumawardani, Oktavia; Undarwati, Anna (Journal of Educational, Health and Community Psychology, 2024)
Non-communicable diseases (NCDs) such as obesity are on the rise in Indonesia. This increase is suspected to be because individuals are unable to maintain healthy food choices. It is hypothesized that personal factors, such as knowledge and attitudes towards food safety, can influence individuals in selecting healthy foods. This study is designed to investigate the influence of knowledge and attitudes towards food safety on healthy food choices among individuals. The research design used is a quasi-experimental study in a laboratory setting using a Fake Food Buffet. The targeted number of participants is 146 university students. This study shows that knowledge and attitudes towards food safety significantly influence healthy food choices. Additionally, knowledge of food safety partially influences healthy food choices. However, attitudes towards food safety do not influence healthy food choices. These findings are important considerations in designing interventions to increase public knowledge about food safety issues, which can reduce the incidence of non-communicable diseases in the future.